2014
DOI: 10.1371/journal.pone.0099107
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Abiotic Environmental Conditions and Herbivory in Shaping Bacterial Community Composition in Floral Nectar

Abstract: Identifying the processes that drive community assembly has long been a central theme in ecology. For microorganisms, a traditional prevailing hypothesis states that “everything is everywhere, but the environment selects”. Although the bacterial community in floral nectar may be affected by both atmosphere (air-borne bacteria) and animals as dispersal vectors, the environmental and geographic factors that shape microbial communities in floral nectar are unknown. We studied culturable bacterial communities in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 54 publications
2
43
0
Order By: Relevance
“…), and Leuconostoc (Álvarez‐Pérez and Herrera , Samuni‐Blank et al. ). Others belong to families that have been isolated from floral tissue, including Enterobacteriaceae (Jacquemyn et al.…”
Section: Resultsmentioning
confidence: 99%
“…), and Leuconostoc (Álvarez‐Pérez and Herrera , Samuni‐Blank et al. ). Others belong to families that have been isolated from floral tissue, including Enterobacteriaceae (Jacquemyn et al.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike other systems where bacterial dispersal is difficult or near impossible to track, our flower visitor -plant -floral bacteria system allowed us to construct a detailed network of potential microbial vectors to plant hosts. Previous studies have used visitor guilds or observed single plant species to link visitor composition to variation in microbial community structure , Samuni-Blank et al 2014) but this study offers detailed species-level identification of floral visitors including predators and parasitoids across a relatively diverse coflowering plant community. This rich dataset allowed us to examine the relative contribution of each taxonomic guild of floral visitors.…”
Section: Discussionmentioning
confidence: 99%
“…However, poor vectors of pollen could be just as effective in vectoring microbes as pollinators. Previous work has shown that herbivores (Samuni-Blank et al 2014) and nectar robbers (Zemenick et al 2018) have distinct effects on microbial community composition. In the current study, a strong correlation between non-bee Hymenoptera and floral bacterial communities (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…T , N8PO1 and N8PI1 were isolated from the mirid bug Capsodes infuscatus during the course of a study on bacterial communities in floral nectar of Asphodelus aestivus plants (Samuni-Blank et al, 2014). Capsodes infuscatus bugs (Hemiptera: Miridae) deposit eggs inside the inflorescence stalk of its host (Asphodelus aestivus).…”
Section: Strains N6po6mentioning
confidence: 99%